Poly(amino acid)-based fibrous scaffolds modified with surface-pendant peptides for cartilage tissue engineering - Svobodová, Jana; Proks, Vladimír; Karabiyik, Özge; Çalıkoğlu Koyuncu, Ayse Ceren; Torun Köse, Gamze; Rypáček, František; Studenovská, Hana (Journal of tissue engineering and regenerative medicine, 2017)
In this study, fibrous scaffolds based on poly(γ-benzyl-l-glutamate) (PBLG) were investigated in terms of the chondrogenic differentiation potential of human tooth germ stem cells (HTGSCs). Through the solution-assisted bonding of the fibres, fully connected scaffolds with pore sizes in the range 20-400 µm were prepared. Biomimetic modification of the PBLG scaffolds was achieved by a two-step reaction procedure: first, aminolysis of the PBLG fibres' surface layers was performed, which resulted in an increase in the hydrophilicity of the fibrous scaffolds after the introduction of N5 -hydroxyethyl-l-glutamine units; and second, modification with the short peptide sequence azidopentanoyl-GGGRGDSGGGY-NH2 , using the 'click' reaction on the previously modified scaffold with 2-propynyl side-chains, was performed. Radio-assay of the 125 I-labelled peptide was used to evaluate the RGD density in the fibrous scaffolds (which varied in the range 10-3 -10 pm/cm2 ). All the PBLG scaffolds, especially with density 90 ± 20 fm/cm2 and 200 ± 100 fm/cm2 RGD, were found to be potentially suitable for growth and chondrogenic differentiation of HTGSCs. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: zubní zárodek; kultivované buňky; Tissue Engineering; Adolescent; Benzyl Compounds; Cells, Cultured; Cell Proliferation; Glycosaminoglycans; peptidy; Tissue Scaffolds; Magnetic Resonance Spectroscopy; lidé; click chemie; glykosaminoglykany; benzylové sloučeniny; chrupavka; Humans; Child; kmenové buňky; Click Chemistry; Glutamates; povrchové vlastnosti; proliferace buněk; viabilita buněk; magnetická rezonanční spektroskopie; Peptides; tkáňové podpůrné struktury; Stem Cells; tkáňové inženýrství; Tooth Germ; dítě; Surface Properties; Cartilage; mladiství; Cell Survival; glutamáty